CTLA‐4 expressed by FOXP3(+) regulatory T cells prevents inflammatory tissue attack and not T‐cell priming in arthritis - Klocke, Katrin (Immunology, 2017)
Cytotoxic T‐lymphocyte antigen 4 (CTLA‐4) ‐mediated regulation of already tolerized autoreactive T cells is critical for understanding autoimmune responses. Although defects in CTLA‐4 contribute to abnormal FOXP3(+) regulatory T (Treg) cell function in rheumatoid arthritis, its role in autoreactive T cells remains elusive. We studied immunity towards the dominant collagen type II (CII) T‐cell epitope in collagen‐induced arthritis both in the heterologous setting and in the autologous setting where CII is mutated at position E266D in mouse cartilage. CTLA‐4 regulated all stages of arthritis, including the chronic phase, and affected the priming of autologous but not heterologous CII‐reactive T cells. CTLA‐4 expression by both conventional T (Tconv) cells and Treg cells was required but while Tconv cell expression was needed to control the priming of naive autoreactive T cells, CTLA‐4 on Treg cells prevented the inflammatory tissue attack. This identifies a cell‐type‐specific time window when CTLA‐4‐mediated tolerance is most powerful, which has important implications for clinical therapy with immune modulatory drugs.